Nationalism Without a State: A Comparative Analysis of Revolutionary Nationalism Among Stateless Nations - Mayet, Humairaa (University of the Witwatersrand, Johannesburg, 2023)
A political philosophy employed by nationalist groups and parties, revolutionary nationalism, is used to resist the established order and achieve political goals. It is especially prevalent when power is held by a group or party which attempts to oppress and stifle certain identities and nationalities while enabling others. Revolutionary nationalism has been practiced by the people of Palestine and Western Sahara, both when they resisted against their European colonisers, Britain and Spain, and today, as they resist against their occupiers, Israel and Morocco. Forms of resistance practices include popular and organised resistance, as well as violent and nonviolent resistance. Similarities and differences emerge when analysing how each of these occupied populations attempted to resist through means of revolutionary nationalism and these can be examined and compared. Revolutionary nationalism often goes hand-in-hand with the expression of the right to self-determination, the highest form of which is statehood. The aim of this research report is to discern whether or not the practices of revolutionary nationalism give rise to self-determination, even though it has been proven that, in the post-Cold War era, they do not give rise to statehood.
A research report submitted in partial fulfilment of the requirements for the degree of Master of arts in international relations to the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2024
Keywords: Palestine; Western Sahara; Marxism; Occupation; Violence; Non-violence; Resistance; UCTD; SDG-16: Peace, justice and strong institutions